Image classification with dense SIFT sampling: an exploration of optimal parameters - Chavez, Aaron J. (Kansas State University, 2012)
In this paper we evaluate a general form of image classification algorithm based on dense SIFT sampling. This algorithm is present in some form in most state-of-the-art classification systems. However, in this algorithm, numerous parameters must be tuned, and current research provides little insight into effective parameter tuning. We explore the relationship between various parameters and classification performance. Many of our results suggest that there are basic modifications which would improve state-of-the-art algorithms. Additionally, we develop two novel concepts, sampling redundancy and semantic capacity, to explain our data. These concepts provide additional insight into the limitations and potential improvements of state-of-the-art algorithms.
Keywords: Image classification; SIFT; PASCAL Visual Object Classes Challenge; Computer Science (0984)